Incidence and distribution of Leek yellow stripe virus in Allium crops in Serbia - Vučurović, Ivan; Nikolić, Dušan; Radović, Nikola; Vučurović, Ana; Ristić, Danijela; Krstić, Branka; Stanković, Ivana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Leek yellow stripe virus (LYSV) is one of the most frequent and important viruses in leek and garlic crops worldwide. In Serbia this virus is found both in leek and garlic, and often at high percentages. During two consecutive years, 2012 and 2013, a total 92 samples were collected from 11 inspected leek-, garlic- and onion-growing locations and they were analyzed for the presence of LYSV using DAS-ELISA. LYSV was detected in 31.5% of the tested samples. In 2012, the presence of LYSV was only detected in leek plants, and in 55.6% of the tested samples. During 2013, LYSV was detected in 85% of leek and 58.3% of garlic samples. In total, LYSV was detected in 56.4% of leek samples and 17.1% garlic samples. LYSV incidence was confirmed using RT-PCR with LYSV specific primers amplifying 1020 bp fragment representing coat protein and part of nuclear inclusion B genes. Molecular identification was confirmed by sequencing of two selected isolates, 181-13 (MG242625) from garlic and 298-13 (MG242624) from leek, and comparing them to the GenBank sequences of LYSV. Phylogenetic analysis of 55 sequences of LYSV from all over the world showed some correlation between host plant and geographical origin of the isolates, forming five separate clades. Two Serbian LYSV isolates fell into distant clades. The Serbian leek isolate 298-13 of LYSV belongs to clade B, while isolate 181-13 originating from garlic belongs in clade E.
Keywords: Leek yellow stripe virus; Leek; Garlic; RT-PCR; ELISA; Serbia